2000
DOI: 10.1021/ja990033i
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Spectra of H+(H2O)5-8 Clusters:  Evidence for Symmetric Proton Hydration

Abstract: Protonated water clusters, H + (H 2 O) n (n ) 5-8), from a supersonic expansion have been investigated by vibrational predissociation spectroscopy and ab initio calculations. The experimental spectra were obtained at an estimated cluster temperature of 170 ( 20 K. Recorded absorption bands at the frequency range of 2700-3900 cm -1 are attributed to the free-and hydrogen-bonded-OH stretches of the ion core and the surrounding solvent molecules. Ab initio calculations, performed at the B3LYP/6-31+G* level, indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

66
428
0
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 342 publications
(497 citation statements)
references
References 52 publications
66
428
0
3
Order By: Relevance
“…38,39 Notably, all of the spectra show 3 distinct features centered at ν 0 ) 3740, 3715, and 3650 cm -1 , corresponding respectively to the asymmetric, the 2-coordinated, and the symmetric free-OH stretches of the water molecules in either the first solvation shell or the second solvation shell of the H 3 O + or H 5 O 2 + ion core. 18 The full widths at half-maximum (fwhm) of these three absorption bands are all larger than 15 cm -1 , but they decrease significantly when H 2 is introduced into the storage cell. An average reduction factor of 1.7 is found for the spectrum acquired at 200 K compared to that at 77 K. Table 2 lists the spectral assignment, vibrational frequencies, and bandwidths of the individual peaks observed at three different bath temperatures in comparison to those obtained at room temperature without H 2 buffer gas.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…38,39 Notably, all of the spectra show 3 distinct features centered at ν 0 ) 3740, 3715, and 3650 cm -1 , corresponding respectively to the asymmetric, the 2-coordinated, and the symmetric free-OH stretches of the water molecules in either the first solvation shell or the second solvation shell of the H 3 O + or H 5 O 2 + ion core. 18 The full widths at half-maximum (fwhm) of these three absorption bands are all larger than 15 cm -1 , but they decrease significantly when H 2 is introduced into the storage cell. An average reduction factor of 1.7 is found for the spectrum acquired at 200 K compared to that at 77 K. Table 2 lists the spectral assignment, vibrational frequencies, and bandwidths of the individual peaks observed at three different bath temperatures in comparison to those obtained at room temperature without H 2 buffer gas.…”
Section: Resultsmentioning
confidence: 97%
“…Identification of them has been successful in a coronadischarged supersonic expansion in our previous experiment. 18 Because the source condition used by this new spectrometer is similar to that of the room-temperature 8-pole ion trap apparatus used in ref 18, we expect that these two chainlike isomers exist in the present 22-pole ion trap mass spectrometer as well.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The structure of protonated water cluster have been the subject of recent experimental studies [1][2][3][4][5][6] . In this work, we have chosen to investigate the structure of H + (H 2 O) 6 by examining the low-lying minima with first principle methods for several reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al examined seven isomers with B3LYP/6-31+G* and concluded that the 402 structure is the most stable form after including ZPE corrected under harmonic oscillator approximation 1 . Their conclusion is supported by the high-level ab initio calculations by Mella et al 14 .…”
Section: Introductionmentioning
confidence: 99%